Technopreneurship Education, Occupational Counselling, and Sustainable Development in Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2023)
Innovation and creativity are basic necessities for any functional education like entrepreneurship education which is skill-based. The method of instructional delivery should be technologically inclined where the scientific knowledge will be inculcated in it. Technopreneurship is a process of acquiring knowledge, skills, and competencies for venture creation through technological knowhow.  Technology is what makes life easier to live.  It is the scientific knowledge used in practical ways to meet and satisfy human needs. Occupational counselling is the guidance and information necessary for all individuals in the world of works for better understanding of self, personality type and acquisition of relevant qualification in relation to entrepreneurship skills, job productivity, satisfaction and overall wellbeing on the work performance.  This paper, therefore, focuses on how technology entrepreneurship and occupational counselling can bring sustainable development to entrepreneurs in their business operations in the global market.  The paper looked at the concept of entrepreneurship, entrepreneurs, technopreneurship, development of entrepreneurship, acquisition of occupational information relevant for building entrepreneurship skills in Nigeria, significance of technology in the operations of modern entrepreneur, roles of technology-based entrepreneurship in economic development, teaching entrepreneurship education using project-based learning method and development of all  related psychological characteristics the individual needs for sustainable development.  The paper concluded that technopreneur, in order to succeed, needs to be taught technology-based entrepreneurship that encourages creativity and Innovation, the importance of understanding self in relation to job satisfaction and productivity that bring about commercialization and industrialization towards global marketing.  The paper recommended, among others, that technology-based entrepreneurship education and occupational counselling should be entrenched into the curriculum right from Basic Schools to Tertiary institutions.  It further stated that supports should be given to Tertiary institutions for curriculum overhauling and development of lecturers in form of training and retraining for sustainability.